Le comité de mendicité mandaté par la nation : vers une harmonisation de la politique d’assistance des valides (1790-1791) - Jean-Baptiste Masméjan (Cahiers Jean Moulin)
1789 Parlementary Revolution provides some huge prerogative to its members, then representative of the French Nation : their will is not only to generate it but also to write a constitution. The brand new National conceptualisation caters an intellectual frame to their project, highlighting the necessity to secularize the assistance and to mutualise the means in order to strive for some new principle that is to aim for equality between the citizens ; this radically new conception marks the schim with the Old Regime’s assitance policy as well as the policies applied by the other Nations. The parlementarians’ work signs National solidarity’s beginning, even if, according to the valid workers, the homo eoconomicus marks the work ethics peak, making inescapable the secularisation of the assistance and its substitution by the State, thus spreading away Christian charity. Moreover, private charity’s entrance in the said support balances National’s solidarity structure, taking in consideration that the right to the assistance depends on private funds, whose allocation follows the benefactors’ goodwills. Labour Law’s emergence, taken aside, is not yet discussed, parliament Members will deal with it during the National Convention occuring in 1792.